The Economic Returns to Social Interaction: Experimental Evidence from Microfinance - Feigenberg, B.; Field, E.; Pande, R. (Review of Economic Studies, 2013)
Microfinance clients were randomly assigned to repayment groups that met either weekly or monthly during their first loan cycle, and then graduated to identical meeting frequency for their second loan. Long-run survey data and a follow-up public goods experiment reveal that clients initially assigned to weekly groups interact more often and exhibit a higher willingness to pool risk with group members from their first loan cycle nearly 2 years after the experiment. They were also three times less likely to default on their second loan. Evidence from an additional treatment arm shows that, holding meeting frequency fixed, the pattern is insensitive to repayment frequency during the first loan cycle. Taken together, these findings constitute the first experimental evidence on the economic returns to social interaction, and provide an alternative explanation for the success of the group lending model in reducing default risk.